CESA TRAFFICKING INHIBITOR Inhibits Cellulose Deposition and Interferes with the Trafficking of Cellulose Synthase Complexes and Their Associated Proteins KORRIGAN1 and POM2/CELLULOSE SYNTHASE INTERACTIVE PROTEIN1. Issue 2 (22nd December 2014) - Worden, Natasha; Wilkop, Thomas E.; Esteve, Victor Esteva; Jeannotte, Richard; Lathe, Rahul; Vernhettes, Samantha; Weimer, Bart; Hicks, Glenn; Alonso, Jose; Labavitch, John; Persson, Staffan; Ehrhardt, David; et al.
Abstract : The compound CESTRIN reduces cellulose content and inhibits the trafficking of CESA in Arabidopsis hypocotyls. Abstract: Cellulose synthase complexes (CSC s) at the plasma membrane (PM ) are aligned with cortical microtubules (MT s) and direct the biosynthesis of cellulose. The mechanism of the interaction between CSC s and MT s, and the cellular determinants that control the delivery of CSC s at the PM, are not yet well understood. We identified a unique small molecule, CESA TRAFFICKING INHIBITOR (CESTRIN), which reduces cellulose content and alters the anisotropic growth of Arabidopsis ( Arabidopsis thaliana ) hypocotyls. We monitored the distribution and mobility of fluorescently labeled cellulose synthases (CESA s) in live Arabidopsis cells under chemical exposure to characterize their subcellular effects. CESTRIN reduces the velocity of PM CSC s and causes their accumulation in the cell cortex. The CSC -associated proteins KORRIGAN1 (KOR1) and POM2/CELLULOSE SYNTHASE INTERACTIVE PROTEIN1 (CSI1) were differentially affected by CESTRIN treatment, indicating different forms of association with the PM CSC s. KOR1 accumulated in bodies similar to CESA ; however, POM2/CSI1 dissociated into the cytoplasm. In addition, MT stability was altered without direct inhibition of MT polymerization, suggesting a feedback mechanism caused by cellulose interference. The selectivity of CESTRIN was assessed using a variety of subcellular markers for which no morphological effect was observed. The association of CESA s with vesicles decorated by the trans-Golgi network-localized protein SYNTAXIN OF PLANTS61 (SYP61) was increased under CESTRIN treatment, implicating SYP61 compartments in CESA trafficking. The properties of CESTRIN compared with known CESA inhibitors afford unique avenues to study and understand the mechanism under which PM -associated CSC s are maintained and interact with MT s and to dissect their trafficking routes in etiolated hypocotyls.